ANALISIS YURIDIS MENGENAI KETERWAKILAN NEGARATERHADAP ORGANISASI INTERNASIONAL DITINJAU DARI HUKUM INTERNASIONAL - Wira Paskah; Chairul Bariah; Arif Arif (Journal of USU International Law, 2017)
ABSTRACT International Organization is a form of a collection of countries as members established under agreements agreed upon by each party and have the same objectives and have rights and obligations in the activities of that organization. In this case, including one for the representation of an international organization. One form of representation in international organizations is to send representatives to other countries. Back diplomatic that has been done since the first. A diplomatic representative is considered a representative of the state in a country's representation of an international organization. The method used is normative juridical, ie research conducted on applicable legal norms, both legal norms derived from national law as well as legal norms derived from international law. The normative juridical research method is a scientific procedure for discovering truth based on the analytical nature, behavior and norms of international law, the relationship with the representation of the state against international organizations. Based on this study, it can be concluded about the state's attachment to an international organization that has been regulated in the Vienna Convention 1975 (Vienna Convention on the Representation of States in Relation to the International Organization with Universal Character 1975. The State's representation of the international organization itself becomes a right. Is responsible for the international organization in which it further clarifies the existence of international organizations. Keywords: International Organization, Vienna Convention 1975, Representation Country